Implementation of Peraturan Bersama Nomor Perber/01/III/2014/BNN Using Therapeutic Community Method Towards Convicted of Drugs Offenders (Study in Narcotics Penitentiary Class IIa Bandar Lampung) - Anggalana*, Anggalana; Oktarina, Amalia (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The Narcotics Correctional Institution has the main objective of dealing with the problem of narcotics, including breaking the network of illegal drugs circulation within the Correctional Institution. The institution also provides health and dependency care for inmates of the correctionl facility. Narcotics Penitentiary Class IIA  Bandar Lampung has specific conditions, namely narcotics abuse convicts as residents, it is appropriate to implement a therapy and rehabilitation program. One of the techniques of therapy and rehabilitation methods is the Therapeutic Community Method. Research problems are the implementation of the Therapeutic Community Method in Narcotics Penitentiary Class IIA  Bandar Lampung and the obstacles in applying the Therapeutic Community Method to inmates of drugs offenders in Narcotics Penitentiary Class IIA  Bandar Lampung. Normative and empirical juridical approaches are used in this research, normative juridical approaches are carried out by studying norms or rules, while the empirical approach is carried out by interviewing informants. Based on indicators of the success of the social rehabilitation program using the Therapeutic Community method, all social rehabilitation participants using the Therapeutic Community method are in a substance-free condition (abstinence) and none of them repeat narcotic crimes (recidivist). The inhibiting factor for the social rehabilitation activities of the Therapeutic Community method in Narcotics Penitentiary Class IIA  Bandar Lampung are the lack of supporting facilities and infrastructure, it often causes the implementation of the program to not running smoothly.